2021
DOI: 10.1088/1361-6528/ac0473
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic streaming of microparticles using graphene-based interdigital transducers

Abstract: Surface acoustic wave (SAW) devices offer many benefits in chemistry and biomedicine, enabling precise manipulation of micro-droplets, mixing of liquids by acoustic streaming and pumping of liquids in enclosed channels, while presenting a cost-effective and easy fabrication and integration with electronic devices. In this work, we present microfluidic devices which use graphene-based interdigital transducers (IDTs) to generate SAWs with a frequency of 100 MHz and an amplitude of up to 200 pm, which allow us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Many studies to date have reported on the efficient manner by which large (micron-sized) particlesprimarily those with relatively low density such as PS particles and cellsare rapidly concentrated in a sessile droplet by the SAW microcentrifugation flow, as typically shown for 5 μm PS particles in Figure a. On the other hand, the challenges associated with concentrating particles below 1 μmagain, primarily those with relatively low densityunder the same microcentrifugation flow have also been well documented .…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies to date have reported on the efficient manner by which large (micron-sized) particlesprimarily those with relatively low density such as PS particles and cellsare rapidly concentrated in a sessile droplet by the SAW microcentrifugation flow, as typically shown for 5 μm PS particles in Figure a. On the other hand, the challenges associated with concentrating particles below 1 μmagain, primarily those with relatively low densityunder the same microcentrifugation flow have also been well documented .…”
Section: Results and Discussionmentioning
confidence: 95%
“…We opt here to adopt an active actuation strategy to avoid the complex and costly nanofabrication of on-chip flow structures and since it allows a higher degree of operational controllability and tunability by varying the external field intensity. Among the various active microcentrifugation schemes that have been reported to date, which also include bulk acoustic wave devices, , surface acoustic waves (SAWs)nanometer amplitude electromechanical Rayleigh waves that propagate along the surface of a piezoelectric substrateand their hybrid surface and bulk wave counterpart, namely, surface reflected bulk waves (SRBWs), have been demonstrated to be particularly adept at driving, among a myriad of microfluidic particle manipulation and flow actuation schemes, intense microcentrifugation flows by breaking the symmetry of the wave to effect rapid and efficient micromixing and localized particle trapping and concentration in a completely integrated and portable chipscale device …”
Section: Introductionmentioning
confidence: 99%
“…3b and show similar conductivities. Although the graphene and PEDOT:PSS devices had lower conductivities than the silver nanowire printed devices, with further device optimization, the thin and light graphene can mitigate mass-loading effects to reduce the inertia of the interdigital transducer 81 83 , and PEDOT:PSS could be further utilized for transparent interdigital transducers, as shown by the images in Supplemental Fig. 1c .…”
Section: Resultsmentioning
confidence: 99%